Lost and found - Clements, Andrew, 1949-; Nobbs, Keith, 1979- (New York : Audioworks, 2008)
The Grayson twins are moving to a new town again. Although it's a drag to be constantly mistaken for one another, still, during those first days at a new school, there's nothing better than a twin brother. But on the first day of sixth grade, Ray stays home sick, and Jay is on his own. Jay quickly discovers a major mistake; no one at this school knows a thing about his brother. Jay almost tells a teacher, but decides that this lost information could be very...useful. And fun.
Compact disc.
Unabridged.
Massachusetts Children's Book Award nominee, 2011-2012.
Producer and director, Amre Klimchak.
Read by Keith Nobbs.
Ages 8-12.
Keywords: Twins -- Juvenile fiction; Brothers -- Juvenile fiction; Identity (Philosophical concept) -- Juvenile fiction; Individuality -- Juvenile fiction; Schools -- Juvenile fiction; Moving, Household -- Juvenile fiction; Twins -- Fiction; Brothers -- Fiction; Identity -- Fiction; Individuality -- Fiction; Schools -- Fiction; Moving, Household -- Fiction; Ohio -- Juvenile fiction; Ohio -- Fiction; Audiobooks; Children's audiobooks